Errors in Students' Writing Composition in Simple Present Tense “MY DAILY ACTIVITY” - Tira Nur Fitria (EDULANGUE, 2019)
ABSTRACT This research is to find out the types of error analysis found in the Students’ Writing Composition in the aspect of grammar, punctuation and spelling also is to find out the most dominant kind of error analysis found in Students’ Writing Composition in Simple Present Tense form. This study applies the quantitative and qualitative methods. This study used documentation as a method of collecting data. From the analysis of this research, it shows that the students’ error in writing composition of simple present tense consists of three aspects of writing, they are they are in grammar, punctuation and spelling. In the aspect of grammar, there are 66 data or 56.89 %, which consist of some errors in class words (part of speech) such as in in verb (25 data or 37.88 %), determiner/article (16 data or 24.24 %), preposition (15 data or 13.64 %), noun (9 data or 13.64 %) and pronoun (1 data or 1.51 %). In punctuation, there are 28 data or 28.14 %, while in spelling there are 22 data or 18.97 %.